KAJIAN MODEL DAN PROTOTIPE SCHEMA MATCHING (Studi untuk Menemukan Peluang Pengembangan Model dan Prototipe Baru) - Edhy Sutanta; Retantyo Wardoyo; Khabib Mustofa; Edi Winarko (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2015)
Abstract—Schema matching is critical problem within manyapplications to integration of data / information, to achieveinteroperability, and other cases caused by schematic heterogeneity.Models and the schema matching methods evolved from manualway on a specific domain, leading to a new models and methodsthat are semi-automatic and more general, so it is able to effectivelydirect the user within generate a mapping among elements of twothe schema or ontologies better. This paper is a summary ofliterature review on research and publication on models, methods,and prototypes on schema matching within the last 25 years todescribe the progress of and research opportunities on a newmodels, methods, and prototypes.Keywords—model, hybrid model, prototipe, schema matching